MULTIVARIATE PERSPECTIVE FOR INVESTIGATING RELATIONS AMONG SOME BEHAVIORAL TRAITS AND FEED PROGRAMS - S. Yiit; M. Mende_ (Journal of Animal and Plant Sciences, 2018)
The main objective of this study is to evaluate the effect of different feed restrictions on some behavioral traits of broiler chickens by using a graphical technique namely Multidimensional Scaling Technique. Multidimensional Scaling Technique indicated that the behavioral traits varied based on feed restrictions and observation time of the behaviors. Results of Multidimensional Scaling Technique also showed that the birds in NF group were more active than the birds in the AD and FR groups and this case was more obvious for males. advantages of the Multidimensional Scaling Technique,
Keywords: Multidimensional scaling technique; multivariate statistics; feed restriction; behavioral traits; correlation.